Microbiota, Oral Microbiome, and Pancreatic Cancer - Michaud, Dominique S. (2014)
Only 30% of patients diagnosed with pancreatic cancer survive one year post-diagnosis. Progress in understanding the causes of pancreatic cancer has been made, including solidifying the associations with obesity and diabetes, and a proportion of cases should be preventable through lifestyle modifications. Unfortunately, identifying reliable biomarkers of early pancreatic cancer has been extremely challenging, and no effective screening modality is currently available for this devastating form of cancer. Recent data suggest the microbiota may play a role in the disease process, but many questions remain. Future studies focusing on the human microbiome, both etiologically and as a marker of disease susceptibility, should shed light on how to better tackle prevention, early detection, and treatment of this highly fatal disease.